Biomechanical analysis of neochordal repair error from diastolic phase inversion of static left ventricular pressurizationCentral MessagePerspective - Matthew H. Park, MS; Mateo Marin-Cuartas, MD; Annabel M. Imbrie-Moore, PhD; Robert J. Wilkerson, BS; Pearly K. Pandya, BS; Yuanjia Zhu, MD, MS; Hanjay Wang, MD; Michael A. Borger, MD, PhD; Y. Joseph Woo, MD (JTCVS Techniques)
Objective: Neochordal implantation is a common form of surgical mitral valve (MV) repair. However, neochord length is assessed using static left ventricular pressurization, leading surgeons to evaluate leaflet coaptation and valve competency when the left ventricle is dilating instead of contracting physiologically, referred to as diastolic phase inversion (DPI). We hypothesize that the difference in papillary muscle (PM) positioning between DPI and physiologic systole results in miscalculated neochord lengths, which might affect repair performance. Methods: Porcine MVs (n = 6) were mounted in an ex vivo heart simulator and PMs were affixed to robots that accurately simulate PM motion. Baseline hemodynamic and chordal strain data were collected, after which P2 chordae were severed to simulate posterior leaflet prolapse from chordal rupture and subsequent mitral regurgitation. Neochord implantation was performed in the physiologic and DPI static configurations. Results: Although both repairs successfully reduced mitral regurgitation, the DPI repair resulted in longer neochordae (2.19 ± 0.4 mm; P < .01). Furthermore, the hemodynamic performance was reduced for the DPI repair resulting in higher leakage volume (P = .01) and regurgitant fraction (P < .01). Peak chordal forces were reduced in the physiologic repair (0.57 ± 0.11 N) versus the DPI repair (0.68 ± 0.12 N; P < .01). Conclusions: By leveraging advanced ex vivo technologies, we were able to quantify the effects of static pressurization on neochordal length determination. Our findings suggest that this post-repair assessment might slightly overestimate the neochordal length and that additional marginal shortening of neochordae might positively affect MV repair performance and durability by reducing load on surrounding native chordae.